INCREASING ACHIEVEMENT IN PKN LEARNING THROUGH ADOBE FLASH BASED LEARNING - Ponidi, Ponidi; Nagara, Erliza Septia; Sinthiya, Ida (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research aims to determine the effectiveness of the Adobe Flash-based learning model in improving student learning achievement in Civics IV subjects at SDN 2 Suka Maju. This classroom action research uses an Adobe Flash-based learning model by developing scientific thinking. This research is a type of Classroom Action Research with pre-cycle stages and 2 cycles, namely cycle 1 and cycle 2 through 4 stages, namely planning, implementation, observation and reflection. The research was conducted at SDN 2 Suka Maju, the subject of this research was 27 students with a KKM success of 76. Data collection techniques were observation, data analysis techniques were using formulas to find out average values ​​and percentages. The research results showed that the learning outcomes in the pre-cycle of learning completeness were 9 students with a percentage of 33%, in the first cycle there was an increase in learning completeness by 13 students, the percentage was 48%, and in the second cycle there were 23 students who achieved the KKM with a success percentage of 85%. . Due to the increase in success in each learning cycle, the author states that the Adobe Flash-based learning model is suitable for use in learning, especially in Civics subjects.